The surgical treatment of traumatic stifle disruption in a cat - Connery, N. A.; Rackard, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
A cat with multiple ligamentous injury of the stifle was surgically managed using a single trans-articular pin. The pin was removed after four weeks with the cat regaining adequate range of motion for normal activity over the following six weeks.
Keywords: Stifle; disruption; cat